Splenic Fc receptor function in host defense and anemia in acute Plasmodium falciparum malaria. - Ho, M; White, N; Looareesuwan, S; Wattanagoon, Y; Lee, S; Walport, M; Bunnag, D; Harinasuta, T (1990)
To determine splenic Fc receptor function in patients with acute Plasmodium falciparum malaria, the clearance of IgG-coated autologous 51Cr-labeled erythrocytes in 20 patients and 10 normal controls was studied. Clearance half-times were directly correlated with both the absolute parasite count (r = .635, P less than .005) and hematocrit (r = .791, P less than .001). Clearance half-times in patients varied from 1.0 to 96.3 h (median, 14.8 h) while those of controls ranged from 8.0 to 80.3 h (median, 23.1 h) (P = .10). Nine of the 20 patients had clearance half-times shorter than the lower 95% confidence limit of controls (less than 12.4 h). The clearance of IgG-coated erythrocytes was accelerated after parasites were eliminated from the circulation (P less than .05) and returned toward normal 6-8 weeks after the acute infection. Although circulating immune complexes were detectable, there was no correlation between immune complex levels and clearance half-times (P greater than .05). The failure to increase Fc receptor-mediated red cell clearance in patients with high parasitemias suggests inadequate splenic phagocytic activity in the face of considerable antigenic challenge. These findings indicate that splenic Fc receptor function may be important both in the control of infection and the development of anemia in P. falciparum malaria.